Sharp Inequalities for Trigonometric Functions. (7th July 2014) - Yang, Zhen-Hang; Jiang, Yun-Liang; Song, Ying-Qing; Chu, Yu-Ming
Abstract : We establish several sharp inequalities for trigonometric functions and present their corresponding inequalities for bivariate means.